Electronic Properties and Ionic Photodissociation of Thionitrite Compounds RSNO [R=(CH3)3C– and (CH3)2CH–]. Issue 5 (21st February 2017) - Cánneva, Antonela; Filho, Reinaldo L. Cavasso; Romano, Rosana M.; Della Védova, Carlos O.; Tong, Shengrui; Ge, Maofa; Erben, Mauricio F.
Abstract: The gas phase electronic properties of thionitrites (RSNO) in both the outermost (valence) and the shallow‐core regions (S 2p) are experimentally studied for the first time by using photoelectron spectroscopy and synchrotron radiation in the VUV range with time‐of‐flight mass spectrometry in the Photoelectron Photoion Coincidence (PEPICO) mode. The He(I) photoelectron spectrum of tert ‐butyl thionitrite, (CH3 )3 CSNO, has been recorded and analyzed with the assistance of quantum chemical calculations. Furthermore, the dissociative photoionization mechanisms for two close related secondary and tertiary species, namely iso ‐propyl thionitrite, (CH3 )2 HCSNO (I ) and (CH3 )3 CSNO (II ), have been determined irradiating gaseous beams with photons in the 155–185 eV range, i. e. exciting and ionizing S 2p electrons of the central –SNO group. The branching ratio of ions produced on this way is analyzed allowing for a clear description of the main fragmentation channels operating after the electronic decay. Abstract : The hitherto unknown electronic properties of thionitrite compounds RSNO are treated in this work which includes photoelectron spectroscopy along with the results of the total ion yield and PEPICO coincidence spectra obtained using synchrotron light. These results are unified and interpreted with those obtained from computational chemistry.